Conformationally restricted monosaccharide-cored glycoside amphiphiles: the effect of detergent headgroup variation on membrane protein stability. - Sadaf,A; Ramos,M; Mortensen,JS; Du,Y; Bae,HE; Munk,CF; Hariharan,P; Byrne,B; Kobilka,BK; Loland,CJ; Guan,L; Chae,PS (ACS Chemical Biology, 2019)
Detergents are widely used to isolate membrane proteins from lipid bilayers, but many proteins solubilized in conventional detergents are structurally unstable. Thus, there is major interest in the development of novel amphiphiles to facilitate membrane protein research. In this study, we have designed and synthesized novel amphiphiles with a rigid scyllo-inositol core, designated scyllo-inositol glycosides (SIGs). Varying the headgroup structure allowed the preparation of three sets of SIGs that were evaluated for their effects on membrane protein stability. When tested with a few model membrane proteins, representative SIGs conferred enhanced stability to the membrane proteins compared to a gold standard conventional detergent (DDM). Of the novel amphiphiles, a SIG designated STM-12 was most effective at preserving the stability of the multiple membrane proteins tested here. In addition, a comparative study of the three sets suggests that several factors, including micelle size and alkyl chain length, need to be considered in the development of novel detergents for membrane protein research. Thus, this study not only describes new detergent tools that are potentially useful for membrane protein structural study but also introduces plausible correlations between the chemical properties of detergents and membrane protein stabilization efficacy.